Housing Finance And Investment In Sub-Saharan Africa: A Case Study Of Malawi - Mzyece, Joel (Graduate School of Business (GSB), 2024)
For many African families, owning a modest home remains a pipe dream. Efforts to address the continent's housing problem are hampered by high costs of urban land and insufficient tenure security, rising building costs, the prevalence of slums and above all a shortage of affordable housing finance. Due to market failure and resource constraints prevalent in the housing sector of Sub-Saharan African (SSA) countries, this study analysed the housing challenges in SSA using data from Malawi, which tends to be dominant with these common factors. With other previous studies which either employ descriptive or qualitative methods, this study additionally contributes by empirically estimating the variables in housing and housing finance using mixed methods analysis. The study's overarching goal was to investigate the impact of financing on housing in SSA using Malawi as a case study. To achieve this objective, the study sought to find answers to the quantitative and qualitative impact of housing finance and other macro and micro variables on housing availability and affordability. Mixed method was used and both the qualitative and quantitative methods were deductive as a priori analyses were done to test what the theoretical and empirical literature entail about housing. Secondary data from World Bank (WB) for the period 1980 to 2020 was used for the quantitative analysis and primary data captured from interviews with government officers and the private sector was used for the qualitative analysis. The findings of the quantitative analysis suggest that government housing finance, interest rate, inflation, GDP growth rate, exchange rate, urban population, and corruption all significantly affect housing. GDP growth rate, exchange rate, and urban population all affect housing positively whilst inflation, interest rate, and corruption affect housing negatively. Refugee population and political instability were found not significant. The findings of the qualitative analysis corroborate that of the quantitative findings. Analysis of interviews shows that interviewees agreed that corruption in government housing finance, interest rate, inflation, and exchange rate, significantly affect housing.